SWOT ANALYSIS OF PT. INDOFOOD SUKSES MAKMUR TBK - Nurul Nadya Ananda Muis; Muhammad Ali; Mursalim Nohong (Paulus Journal of Accounting (PJA), 2023)
Marketing strategy is making decisions about marketing costs, marketing mix, and marketing allocation concerning expected environmental conditions and competitive conditions. This research is qualitative in descriptive form. Qualitative research is a method carried out in natural conditions. The research data collection method was carried out by studying literature from accredited scientific publications and digital news. In this research, a case study was carried out analyzing the SWOT at PT. Indofood Sukses Makmur Tbk. PT Indofood CBP Sukses Makmur Tbk. (ICBP), a subsidiary of PT Indofood Sukses Makmur Tbk. (INDF), highlighting its founding in 2009 through the restructuring of its Consumer Branded Products (CBP) group. ICBP's main focus on the food and beverage sector is evident in the successful integration of four INDF subsidiaries, thereby increasing efficiency and productivity. However, ICBP faces challenges, including dependence on a large workforce, the risk of dependence on imported raw materials, and rapidly changing consumer preferences. The SWOT analysis identified opportunities, such as leveraging digital marketing for millennial engagement, capitalizing on emerging markets, and aligning with the modern consumer's convenient lifestyle. However, companies must face threats such as increasing competition, operational efficiency amidst price wars, potential disruptions in the supply of imported raw materials, and consumer concerns about chemicals in instant noodle products. A comprehensive understanding of these aspects enables ICBP to formulate strategic initiatives that capitalize on growth potential while effectively managing inherent risks.